To Assess Correlation of Fasting Blood Glucose, Hb1Ac and Serum Lipid Level in Type II Diabetes Mellitus Patients (Academia Journal of Medicine, 2019)
Background: Diabetes Mellitus (DM) refers to a group of common metabolic disorder that share the phenotype of hyperglycaemia caused due  to either deficiency of insulin secretion or insulin resistance. The present study was conducted to assess correlation of fasting blood glucose,  Hb1Ac and type II DM in given adults. Subjects and Methods: The present study was conducted on 134 patients with type II diabetes  mellitus (DM) of both genders. Patients were subjected to estimation of fasting and random blood glucose level. Modified method of Fluckiger  and Winterhalter was used for estimation of glycosylated haemoglobin (HbA1C). Results: Out of 134 patients, males were 84 and females  were 50. Age group 20-30 years had 11, 30-40 years had 14, 40-50 years had 38, 50-60 years had 46 and >60 years had 25 patients. The mean  fasting blood glucose level in patients with good degree of control was 106.2, in fair was 164.4 and in poor was 208.2. Glycosylated  hemoglobin level was good (6.74), fair (8.12) and poor (12.54). A positive correlation of fasting blood glucose and glycosylated hemoglobin  level and serum cholesterol & glycosylated hemoglobin level (P< 0.05) was found. Conclusion: Authors found a positive correlation of fasting  blood glucose and glycosylated hemoglobin level and serum cholesterol & glycosylated hemoglobin level in type II diabetes mellitus patients.
Keywords: Diabetes Mellitus; Fasting blood glucose; Glycosylated hemoglobin